Influence of Citric Acid Pretreatment on Drying of Peach Slices - Doymaz, Ibrahim; Bilici, Betul (WALTER DE GRUYTER GMBH, 2014)
The effect of citric acid pretreatment on the drying characteristics of peach slices was investigated in a cabinet dryer. The experiments were conducted on peach slices with a thickness of 5 mm at temperatures of 45, 55, 65 and 75 degrees C with an air velocity of 2.0m/s. The drying time of peach slices pretreated with citric acid solution was shorter than the control ones. The drying data were fitted to five thin-layer drying models. The results show that the Midilli et al. model was the most appropriate model for drying of peach slices. The values of effective moisture diffusivity were found to range between 1.94 x 10(-10) and 8.49 x 10(-10) m(2)/s over the temperature range studied. The values of activation energy were calculated as 36.82 and 37.12 kJ/mol for control and pretreated samples, respectively. Superior rehydration was noticed for citric acid pretreated slices dried at 65 degrees C.
Keywords: citric acid; drying; mathematical modelling; peach; rehydration ratio; MOISTURE DIFFUSIVITY; REHYDRATION KINETICS; SELECTION; FRUITS; Food Science & Technology